2018
DOI: 10.1186/s11671-018-2754-4
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Nanocone Cluster Microstructure with Anti-reflection and Superhydrophobic Properties for Photovoltaic Devices

Abstract: As three-dimensional (3D) nanostructures can significantly improve the absorption capacity of photons, it is widely used in various photovoltaic devices. However, the high-cost and complex preparation process of traditional 3D nanostructures restricted its development greatly. In this paper, a new type of nanocone cluster microstructure was prepared on polydimethylsiloxane (PDMS) substrate by using a simple template process. This novel nanocone cluster microstructure can significantly improve the light transmi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…The devices showed an obvious PCE improvement after laminating the textured PDMS films, as previously reported. [ 71–73 ] We noticed that the highest efficiency improvement was achieved based on 6k‐PDMS, which exhibited both high diffused transmittance and haze effect, which is much less studied in transparent OPV so far. This PCE enhancement was attributed to the synergy of the anti‐reflection and extended effective optical path lengths by haze, [ 74 ] which enabled the higher photocurrent in a certain active layer thickness.…”
Section: Resultsmentioning
confidence: 99%
“…The devices showed an obvious PCE improvement after laminating the textured PDMS films, as previously reported. [ 71–73 ] We noticed that the highest efficiency improvement was achieved based on 6k‐PDMS, which exhibited both high diffused transmittance and haze effect, which is much less studied in transparent OPV so far. This PCE enhancement was attributed to the synergy of the anti‐reflection and extended effective optical path lengths by haze, [ 74 ] which enabled the higher photocurrent in a certain active layer thickness.…”
Section: Resultsmentioning
confidence: 99%
“…A literature review showed that conically shaped structures show various properties and, therefore, can be applied in other fields. Nanoconical 3D a-Si and polydimethylsiloxane structures show interesting optical anti-reflection properties and can be used in photonics [117,118]. Conical Co microstructures can be applied in low-temperature solid-state bonding [53].…”
Section: Applicationsmentioning
confidence: 99%
“…Recently, researchers have found that a bio-inspired moth-eye nanostructure exhibits outstanding broadband low reflectivity and high transmission with wide-angle incident light compared to conventional antireflective multilayer coatings [8][9][10][11][12][13][14][15][16]. This kind of bio-inspired nanostructure is considered an effective way to enhance the photoconversion efficiency of solar cells [17][18][19][20] or the visibility of displays [21][22][23].…”
Section: Introductionmentioning
confidence: 99%